2022
DOI: 10.1016/j.celrep.2021.110212
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota of environmentally enriched mice regulates visual cortical plasticity

Abstract: Exposing animals to an enriched environment (EE) has dramatic effects on brain structure, function, and plasticity. The poorly known ''EE-derived signals'' mediating the EE effects are thought to be generated within the central nervous system. Here, we shift the focus to the body periphery, revealing that gut microbiota signals are crucial for EE-driven plasticity. Developmental analysis reveals striking differences in intestinal bacteria composition between EE and standard rearing (ST) mice, as well as enhanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 93 publications
2
24
0
Order By: Relevance
“…Thus, the regulation of FS-PV cell activity is uniquely positioned by integrating information coming from systemic and circadian signals, from local and choroid-plexus-derived molecular signals, and from local and long-range synaptic inputs. Although not highlighted in this review, other factors, such as changes in inflammatory response due to early-life stress or changes in gut bacteria, have recently been shown to affect CPs (Smith et al, 2016 ; Ikezu et al, 2021 ; Lupori et al, 2022 ). Many questions remain, such as whether FS-PV cells act in concert with local glial cells by regulating the secretion of glial-derived factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the regulation of FS-PV cell activity is uniquely positioned by integrating information coming from systemic and circadian signals, from local and choroid-plexus-derived molecular signals, and from local and long-range synaptic inputs. Although not highlighted in this review, other factors, such as changes in inflammatory response due to early-life stress or changes in gut bacteria, have recently been shown to affect CPs (Smith et al, 2016 ; Ikezu et al, 2021 ; Lupori et al, 2022 ). Many questions remain, such as whether FS-PV cells act in concert with local glial cells by regulating the secretion of glial-derived factors.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences have revealed that intestinal microbiota may be a possible therapeutic or preventive candidate for hyperglycemia, dyslipidemia, pre-diabetes and NAFLD ( Lupori et al, 2022 ). It was previously reported that high-energy diet-feeding may lead to significant reduce of the relative abundance of beneficial microbial phylotypes in intestinal tract, including Lactobacillus , Bifidobacterium , Butyricicoccus and Akkermansia ( Guo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This improved plastic phenotype was similar to a phenotype due to an enriched environment (EE), and the removal of GM in EE-exposed mice significantly decreased SCFAs and plasticity. Therefore, it is possible to assume that the GM enhances cerebral plasticity through SCFA-driven microglia remodeling [ 61 ]. If SCFAs are one of the key molecules involved in plasticity, there may be a strong link between SCFAs and EIB modulation.…”
Section: Scfa In Seizure Controlmentioning
confidence: 99%